2019
DOI: 10.1111/dth.13172
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of port wine stain with Tixel ‐induced rapamycin delivery following pulsed dye laser application

Abstract: Although pulsed dye laser (PDL) is considered the gold standard treatment for port wine stains (PWS), post PDL revascularization is one of the main causes of incomplete regression and recurrence. Recently, topical sirolimus have been shown to improve treatment outcome probably through minimizing post-laser revascularization. We sought to evaluate the added value of the Tixel drug delivery system (DDS) to the PDL and topical rapamycin treatment for PWS. This case series includes three teenager patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
(51 reference statements)
1
16
0
Order By: Relevance
“…It has been previously shown that pulse durations around 6 milliseconds are used for drug delivery and those greater than 10 milliseconds are used for rejuvenation; common settings for rejuvenation are 12-14 milliseconds. 11,25,26 As the periorbital region is a sensitive area, coordinating treatment at two centers in different countries with diverse populations warranted more conservative treatment parameters. The depth was chosen based on the depth of the periorbital skin to the reach the papillary dermis ~300 µm (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously shown that pulse durations around 6 milliseconds are used for drug delivery and those greater than 10 milliseconds are used for rejuvenation; common settings for rejuvenation are 12-14 milliseconds. 11,25,26 As the periorbital region is a sensitive area, coordinating treatment at two centers in different countries with diverse populations warranted more conservative treatment parameters. The depth was chosen based on the depth of the periorbital skin to the reach the papillary dermis ~300 µm (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we chose a more conservative approach with a pulse duration of 10 milliseconds and 500 µm protrusion. It has been previously shown that pulse durations around 6 milliseconds are used for drug delivery and those greater than 10 milliseconds are used for rejuvenation; common settings for rejuvenation are 12–14 milliseconds 11,25,26 …”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been a growing sentiment that microneedling may be inferior to lasers and other energy-based modalities for device-assisted drug delivery. Thermomechanical injury has already been used to deliver botulinum toxin to mediate rosacea and Hailey-Hailey disease, 26,27 triamcinolone and 5-fluorouracil to reduce scar size, 28,29 rapamycin for enhanced pulsed dye laser treatment of port-wine stains, 30 and beta blockers for infantile hemangiomas. 31 Depending on the selected treatment parameters, the fractional thermomechanical device can allow for ablative or nonablative histologic effects because of heat transfer from short contact of the 400°C-heated pyramidal tip, 11 which can attain similar ablative temperatures to the CO2 laser.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that hypoxia can result in the activation of two important and potent vascular proliferation patterns, including HIF‐1a and VEGF. Thus, it could be speculated that preventing this hypoxia‐induced revascularization may result in a better outcome of laser treatment 21 . It has been well‐known that mTOR signaling is a crucial pathway in the cellular response to hypoxia by HIF‐1α 10 .…”
Section: Discussionmentioning
confidence: 99%